(untitled) (Journal of Asian Development Studies, 2023)
The current study explores the plight, troubles, and struggle of subalterns and their endeavors to raise their voices against the injustice incurred upon them in the novel Skyfall by award-winning Pakistani author Saba Karim Khan. The current study focuses on subaltern studies and employs the theoretical framework of postcolonial theory. The study aims to indicate ways to fulfill two purposes in which subalterns, particularly female characters, are being marginalized and suppressed due to the power structure of social and cultural factors and the misappropriation of religious teachings, gender, and sexuality. Secondly, it identifies the resistance and fight against oppression and patriarchy. The study is qualitative and uses the text as a primary source of data collection, which is analyzed in the light of Gayatri Spivak’s essay “Can the Subaltern Speak?” Saba Karim Khan has beautifully interwoven themes of oppression, marginalization, gender, and sexuality in the text and portrayal of social, political, economic, and religious forces in shaping the power structure. Data analysis shows that oppression and marginalization are evident through the subaltern characters of protagonist Rania Mirza Kasturi, her mother Jahaan e Rumi, and her sister Ujala. On the other hand, textual evidence from the novel demonstrates that these characters do not always remain silent victims and raise their voices against tyrannical forces to acquire their identity as individuals